Una profezia che si autoavvera. Indipendenza, mercificazione e annientamento nella cultura punk britannica - Brenda FEDI (Diacronie. Studi di Storia Contemporanea)
When, in 1977, the Sex Pistols sang the slogan “No Future”, they were embodying a cultural and generational response to a collective discomfort which resulted from interpreting the political and socioeconomic condition as profoundly unjust and oppressive, but fundamentally unavoidable. The aim of this research is to show that while punks were announcing the end of the future, they were also giving new meaning to practices – such as self-publishing and self-recording – and creating do it yourself networks which outlived the end of the movement and affected and politicized the way of producing and consuming music for the future generations.